Suppression of phospholipase D[Alpha] in soybean - Lee, Jung Hoon (Kansas State University, 2008)
Demands on value-added crops have been raised to improve agricultural, industrial, and economical value. Currently, transgene application is one of most effective methods to satisfy these demands. Success in herbicide-resistant soybean (Glycine max (L.) Merr.) has boosted genetic engineering to be used for biochemical, nutritional, cultural, and physiological improvements. The objectives of this study were to establish transgenic soybean lines with attenuated phospholipase D[Alpha] (PLD[Alpha]) activity in the seed, test the alteration of fatty acid profiles affected by transgene and somaclonal variation, and evaluate the physiological alteration of transgenic lines by both transgene and somaclonal variation. To change fatty acid profile in soybean seed, we attenuated PLD[Alpha] enzyme activity by an RNA interference construct using the PLD[Alpha] gene sequence. Two transgenic soybean lines were established by particle inflow gun bombardment of co-bombarding pSPLDi and pHG1 transgenes, and evaluated for the presence and expression of transgenes thoroughly through the T[subscript]5 generation. PLDα-suppressed soybean lines were characterized by decreased PLD[Alpha] enzyme activity and PLD[Alpha] protein both during seed development and in mature seeds. The PLD[Alpha]-attenuated transgenic lines, SW1-7-1-1 and SW1-7-1-2, contain 36% and 49% oleic acid in the filed and greenhouse evaluations, respectively, which are equivalent to the mid-oleic acid soybean lines improved by conventional breeding and mutagenesis. Phenotypic and genetic analysis of the transgenic lines suggested the possibility that the multi-copy transgene integration formed direct or indirect repeats by random ligation during integration and organization of transgenes in the soybean genome, and the transgene cluster with tandem repeats may consequently increase the probability of transgene silencing. Various factors, such as high humidity and temperature, result in the loss of seed viability. Fayette seed stored for two months since harvest exhibited about 95% viability; however Fayette seeds stored for 33 months at room temperature and uncontrolled relative humidity become non-viable. PLDα-attenuated transgenic soybean seeds have been produced by transformation. PLD-suppressed transgenic soybean seeds have maintained viability when stored for 33 months at room temperature. Germination of transgenic seed stored for 33 months ranged from 30 to 50%. Increased leakage of electrolytes associated with the loss of viability was observed in null-transgenic and background seeds versus transgenic seed. The increase in electrolyte leakage may have been induced by lipid peroxidation and free radical formation which can generate oxidative damage in the cell and subsequently decrease seed viability. Differences in the ultrastructure of cotyledon tissue were observed between PLD[Alpha]-suppressed soybean and the background cultivar. The loss of viability in the background cultivar was consistent with observations of the plasma membrane being detached from the cell wall complex and disorganization of oil bodies. Stresses caused by temperatures higher or lower than ambient are one of agricultural problems that reduce crop productivity in many areas and diverse species. To overcome the uncertainty of environmental fluctuations, efforts continue to improve high and low temperature tolerance in crops. PLD[Alpha]-suppressed transgenic events were produced by antisense suppression driven by constitutive and seed-specific promoters using the particle inflow gun (PIG) bombardment method. Nine fertile transgenic events suppressed the expression of PLD[Alpha] protein. PLD{Alpha] enzyme activity in T[subscript]1 seed was observed to be reduced by 25 percent compared to the non-transgenic control. When soybean seedlings were exposed to lethal freezing temperature, increased electrolyte leakage associated with oxidative damage and biophysical changes were observed in non-transgenic soybean, whereas membrane stability and integrity were maintained in transgenic soybean seedlings. The early growth of PLD[Alpha]-attenuated soybean seedlings was recovered from extreme heat-shock (45 °C) and freezing treatments (-8 °C). The disruption of the plasma membrane and organelles was observed in freeze-stressed non-transgenic control seedlings. On the other hand, the structures of the plasma membrane, oil bodies, and cell organelles in transgenic seedlings were partially sustained after enduring freezing and thawing stresses.
Keywords: soybean; phospholipase D; Agriculture, Agronomy (0285)